FLAVONOID (QUERCETIN) CONTENT, YEAST AND MOLD CONTAMINATION IN DUCK MEAT SOAKED IN SHALLOT (ALLIUM ASCALONICUM) SKIN WASTE - Unzilatirrizqi D, Yan El Rizal; Sri Mukodiningsih; Bambang Cahyono (The Indonesian Journal of Public Health, 2025)
Introduction:  The flavonoid content in shallot skin is 2–10 g/kg higher than that in the edible portion, with < 0.03 to 1 g/kg. Aims: To determine flavonoid (quercetin) content and yeast and mold contamination in duck meat soaked in shallot (Allium ascalonicum) skin waste. Methods: The sample was shallot skin waste from 14 districts in Brebes Regency, Indonesia. Analysis was performed in several steps, including the production of shallot skin flour and measurement of flavonoid (quercetin) levels using a UV-Vis spectrophotometer. This study analyzed the amount of yeast mold growth on duck meat after soaking in shallot skin waste extract and the test data obtained will be analyzed descriptively and presented in the form of a table. Results: The average flavonoid (quercetin) content in the shallot skin waste was 4.33% w/w. The lowest flavonoid (quercetin) content in the Sirampog district was 4.29% w/w and the highest quercetin content was 4.40% w/w in the Wanasari district. The mold and yeast contamination levels varied among treatments, with treatment 1 having the highest contamination rate of 96 colonies/g, followed by treatments 2 and 3 with contamination rates of 20 and 15 colonies/g, respectively, and treatment 4 having contamination rates of 3 colonies per gram. Conclusion: The flavonoid content of shallot skin waste varied across the districts. Mold and yeast contamination levels were significantly different among the treatments, with treatment 1 showing the highest contamination rate. Treatment 4 resulted in a very rapid reduction in the number of molds and yeast (3 colonies).